The Effect of Self-selection on Student Satisfaction and Performance in Online Classes - Yatrakis, Pan G.; Simon, Helen K. (International Review of Research in Open and Distributed Learning, 2002)
This paper examines student performance, satisfaction, and retention of information in online classes as a function of student choice as to the format of instruction. Student outcomes are studied for two groups enrolled in online classes: those who were allowed to choose between an online and a ground-based format and who chose the online format voluntarily; and those who were obliged to take classes in the online format without being afforded the opportunity to choose.